Data from: Circadian rhythmicity persists through the Polar night and midnight sun in Svalbard reindeer - Arnold, Walter; Ruf, Thomas; Loe, Leif Egil; Irvine, R. Justin; Ropstad, Erik; Veiberg, Vebjørn; Albon, Steve D. (Zenodo, 2018)
Studies of locomotor activity in Svalbard reindeer reported the temporary absence of diel rhythms under Arctic photic conditions. However, using Lomb-Scargle periodogram analyses with high statistical power we found diel or circadian rhythmicity throughout the entire year in measures of behaviour, temperature in the rumen and heart rate in free-living Svalbard reindeer. Significant diel rhythmicity was only lacking during some of the 15-day intervals analysed in the less frequently measured heart rate. During Polar Night these rhythms were free-running and attenuated. During continual daylight in summer, rhythms where entrained to 24 hours corresponding with the daily variation in the intensity of solar radiation, but attenuated when continuous daylight coincided with the period of growing forage. Diel rhythmicity was reduced during this short period of peak foraging activity, which coincided with peak heart rate and temperature in the rumen, most likely to facilitate fattening when food is abundant. For the rest of the year, heart rate and temperature showed the most pronounced and long-lasting suppression ever found in ungulates. The profound seasonal changes in foraging, metabolic activity, and power of diel and circadian rhythmicity of Svalbard reindeer can be viewed as adaptations to the extreme living conditions in the High Arctic. NDVI Data NDVI Data for the three study sites 2012-2014 EVI_NDVI one sheet.csv Telemetry data file for the individual recorded HB11187_ID02_Filtered.csv Telemetry data file for the individual recorded HB11229_ID01_Filtered.csv Telemetry data file for the individual recorded HB11245_ID04_Filtered.csv Telemetry data file for the individual recorded HB11373_ID03_Filtered.csv